Copper oxide loaded PLGA nanospheres: towards a multifunctional nanoscale platform for ultrasound-based imaging and therapy. (9th March 2018) - Perlman, Or; Weitz, Iris S; Sivan, Sarit S; Abu-Khalla, Hiba; Benguigui, Madeleine; Shaked, Yuval; Azhari, Haim
Abstract: Copper oxide nanoparticles (CuO-NPs) are increasingly becoming the subject of investigation exploring their potential use for diagnostic and therapeutic purposes. Recent work has demonstrated their anticancer potential, as well as contrast agent capabilities for magnetic resonance imaging (MRI) and through-transmission ultrasound. However, no capability of CuO-NPs has been demonstrated using conventional ultrasound systems, which, unlike the former, are widely deployed in the clinic. Furthermore, in spite of their potential as multifunctional nano-based materials for diagnosis and therapy, CuO-NPs have been delayed from further clinical application due to their inherent toxicity. Herein, we present the synthesis of a novel nanoscale system, composed of CuO-loaded PLGA nanospheres (CuO-PLGA-NS), and demonstrate its imaging detectability and augmented heating effect by therapeutic ultrasound. The CuO-PLGA-NS were prepared by a double emulsion (W/O/W) method with subsequent solvent evaporation. They were characterized as sphere-shaped, with size approximately 200 nm. Preliminary results showed that the viability of PANC-1, human pancreatic adenocarcinoma cells was not affected after 72 h exposure to CuO-PLGA-NS, implying that PLGA masks the toxic effects of CuO-NPs. A systematic ultrasound imaging evaluation of CuO-PLGA-NS, using a conventional system, was performed in vitr o and ex vivo using poultry heart and liver, and also in vivo using mice, all yielding a significant contrast enhancement. In contrast to CuO-PLGA-NS, neither bare CuO-NPs nor blank PLGA-NS possess these unique advantageous ultrasonic properties. Furthermore, CuO-PLGA-NS accelerated ultrasound-induced temperature elevation by more than 4 °C within 2 min. The heating efficiency (cumulative equivalent minutes at 43 °C) was increased approximately six-fold, demonstrating the potential for improved ultrasound ablation. In conclusion, CuO-PLGA-NS constitute a versatile platform, potentially useful for combined imaging and therapeutic ultrasound-based procedures.